Investigation of behaviour of sand-fines mixtures using direct shear (DS) testing and dem simulations - Ospanova, A.; Ulykbanov, A.; Nurbek, Y.; Minh, N. H. (Nazarbayev University, 2014)
The Critical State Framework describes a relationship between the shear strength and the void ratio of a soil and it is mostly applicable to describe the behavior of pure clay and pure sand samples of relatively uniform particle sizes. However, mixtures of different particle size materials do not always follow this theory; the presence of some small particles can destabilize and affect the behavior of those mixtures under the applied shear stress. This Project's main objective is to investigate the effect of the fines content in mixtures of sand and fine particles using Discrete Element Method (DEM) computer simulations and Direct Shear (DS) laboratory testing. Investigation of the effect of the fines content on the force distribution between particles and hence on the shear strength of the materials can be helpful in the prediction of the shear strength and deformation characteristics of granular mixtures in civil engineering and powder industries.
Keywords: DEM simulations; micromechanical; characteristics; direct shear; testing